Pengaruh Teori Belajar Humanistik terhadap Motivasi Belajar Siswa Madrasah Ibtidaiyah: Suatu Systematic Review - Aida Khairani; Nur Saidah; Tiar Anna Sari; Intan Aini Lubis (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study was conducted with the main objective of exploring in depth the impact of the application of humanistic learning theory on increasing students' learning motivation at the Madrasah Ibtidaiyah (MI) level. The study adopted a systematic review approach, which is a research method conducted through the collection, review and analysis of various relevant literature and previous research results that have been published in the last ten years. Through the review of a number of scientific works, it was found that the application of the basic principles of humanistic learning theory which includes aspects of self-actualisation, providing empathy in the process of teaching and learning interactions, as well as an emphasis on student-centred learning processes has a significant contribution to increasing students' intrinsic motivation in following the learning process in MI. This humanistic approach not only has an impact on cognitive aspects, but is also able to foster self-confidence, a sense of security, and a healthy relationship between teachers and students. The results of this systematically compiled study provide important implications for the world of basic education, especially Madrasah Ibtidaiyah, namely the need for integration of humanistic learning theory into the learning strategies and methods used by teachers every day. Thus, the application of the humanistic approach is expected to contribute directly to improving the quality of educational processes and outcomes at the MI level as a whole.